Intrinsic leakage and adsorption currents associated with the electrocaloric effect in multilayer capacitors - Quintero, Mariano Horacio (2015)
During the last few years, the increasing demand of energy for refrigeration applications has relived the interest of the scientific community in the study of alternative methods to the traditional gas-based refrigeration. Within this framework, the use of solid state refrigeration based on the electrocaloric effect reveals itself as one of the most promising technologies. In this work, we analyze how the temperature change associated with the electrocaloric effect shows a correlation with the electrical properties of a commercial multilayer capacitor. In that sense, we established a clear relation between the adsorption currents and the temperature change produced by the electrocaloric effect. Additionally, intrinsic leakage currents are responsible for the sample heating due to the Joule effect. These well distinguished contributions can be useful during the design of solid state refrigeration devices based on the electrocaloric effect.